PERLAKUAN GURU TERHADAP ANAK DISLEKSIA : STUDI MENDALAM DI KELAS III SDN 34 CAKRANEGARA - Audiari, Ni Nyoman Indi Audiari; Witono, A. Hari Witono; Setiawan, Heri (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2024)
In the world of education there are learning difficulties in the learning process, where the inability of students to accept or respond in the learning process, so the necessary role of teachers in dealing with learning difficulties. Difficulty reading is called dyslexia. Dyslexia is a difficulty in analyzing speech, sounds, and difficult to learn about how to combine letters and words which is generally felt in children at primary school age. This study aims to describe the treatment of teachers of dyslexic children in Class III SDN 34 Cakranegara. This study uses qualitative research methods with a descriptive approach. There is also a source of data in this study obtained through observing and interviewing homeroom teachers Grade III. There are three lines of activities that can be carried out in data analysis, namely data reduction, data presentation, and conclusion. The results of the analysis showed that there are 3 backgrounds of children with dyslexia, with characteristics of children who do not understand the form of writing, teachers provide facilities in the form of books, with image media, and multisensory methods, and always provide motivation to children to be confident.